2010
DOI: 10.1038/nature09142
|View full text |Cite
|
Sign up to set email alerts
|

The male mouse pheromone ESP1 enhances female sexual receptive behaviour through a specific vomeronasal receptor

Abstract: Various social behaviours in mice are regulated by chemical signals called pheromones that act through the vomeronasal system. Exocrine gland-secreting peptide 1 (ESP1) is a 7-kDa peptide that is released into male tear fluids and stimulates vomeronasal sensory neurons in female mice. Here, we describe the molecular and neural mechanisms that are involved in the decoding of ESP1 signals in the vomeronasal system, which leads to behavioural output in female mice. ESP1 is recognized by a specific vomeronasal rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
411
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(427 citation statements)
references
References 34 publications
13
411
2
1
Order By: Relevance
“…In this respect, it is interesting to note that, although ESP1 is exclusively produced by the lacrimal gland, the harderian, lacrimal and submaxillary glands produce other peptides of the ESP family that are not expressed in a sexually dimorphic way. At least some of these peptides apparently activate VNO cells (Haga et al, 2010), thus suggesting a role of the ESP peptides in social signalling. For instance, it has recently been described that ESP22 is secreted by lacrimal glands of both male and female mice, in a 50-fold higher concentration in juvenile than adults (Ferrero et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…In this respect, it is interesting to note that, although ESP1 is exclusively produced by the lacrimal gland, the harderian, lacrimal and submaxillary glands produce other peptides of the ESP family that are not expressed in a sexually dimorphic way. At least some of these peptides apparently activate VNO cells (Haga et al, 2010), thus suggesting a role of the ESP peptides in social signalling. For instance, it has recently been described that ESP22 is secreted by lacrimal glands of both male and female mice, in a 50-fold higher concentration in juvenile than adults (Ferrero et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…When detected by vomeronasal organ, ESP1 stimulates lordosis in females (Haga et al, 2010), whereas some MUPs have been shown to elicit aggression and countermarking in males (Chamero et al, 2007;Kaur et al, 2014) and attraction in females (Roberts et al, 2010). In addition, type I MHC peptides, showing low volatility, may also act as chemosignals that allow mate recognition in the context of the induction of pregnancy failure (Bruce effect; Leinders-Zufall et al, 2004).…”
Section: A Volatile Male Sexual Pheromones: Chemical Species and Thementioning
confidence: 99%
See 2 more Smart Citations
“…Pheromones can be short or long range, or act on contact. In house mice, volatile pheromone molecules detected at a distance of centimetres include dehydro-exobrevicomin and 2-sec-butyl-4,5-dihydrothiazole, whereas the non-volatile male peptide pheromone ESP1 (exocrine glandsecreting peptide 1) gets transferred from the male's tear glands to the nose (and thus vomeronasal organ, VNO) of the female during courtship contact [12].…”
Section: Pheromones Are Chemical Signals That Meet Well-established Cmentioning
confidence: 99%